2021
DOI: 10.1101/2021.03.16.435583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parasitic wasps do not lack lipogenesis

Abstract: Fatty acids are crucial primary metabolites for virtually any creature on earth. Therefore, most organisms do not rely exclusively on nutritional supply with fatty acids but have the ability to synthesize fatty acids and triacylglycerides de novo from carbohydrates, a process called lipogenesis. The ubiquity of lipogenesis has been questioned by a series of studies reporting that many parasitic wasps (parasitoids) do not accumulate lipid mass despite having unlimited access to sugar. This has been interpreted … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Due to their parasitic lifestyle, parasitic wasps were assumed to receive sufficient amounts of lipids from their hosts during larval development making the ability to synthesize fatty acids redundantly and finally have led to an evolutionary trait loss (Visser et al, 2010). Labeling studies involving feeding experiments with 13 C-labeled glucose, however, have demonstrated that parasitic wasps are able to convert glucose into palmitic and stearic acid (Prager et al, 2019;Ruther et al, 2021). The present study demonstrates that parasitic wasps possess the enzymatic machinery to not only synthesize these primary products of fatty acid biosynthesis but also to introduce double bonds at positions 9 and 12 to produce OA and LA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their parasitic lifestyle, parasitic wasps were assumed to receive sufficient amounts of lipids from their hosts during larval development making the ability to synthesize fatty acids redundantly and finally have led to an evolutionary trait loss (Visser et al, 2010). Labeling studies involving feeding experiments with 13 C-labeled glucose, however, have demonstrated that parasitic wasps are able to convert glucose into palmitic and stearic acid (Prager et al, 2019;Ruther et al, 2021). The present study demonstrates that parasitic wasps possess the enzymatic machinery to not only synthesize these primary products of fatty acid biosynthesis but also to introduce double bonds at positions 9 and 12 to produce OA and LA.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the detection of 13 C-carbon in LA from organisms fed 13 C-labeled glucose or acetate indicates that the studied organisms possess all enzymes necessary for LA biosynthesis including a Δ12-desaturase Shimizu et al, 2014). Parasitic wasps have long been assumed to lack lipogenesis (Visser & Ellers, 2008;Visser et al, 2010), but recent studies have demonstrated that this is not the case (Prager et al, 2019;Ruther et al, 2021). Hence, stable isotope labeling experiments with 13 C-labeled glucose should be generally suitable to demonstrate LA biosynthesis in parasitic wasps.…”
Section: Introductionmentioning
confidence: 99%
“…We did not consider the M + 2 satellites (PAME m/z 272, SAME m/z 300, OAME: m/z 298, LAME: m/z 296) because of the M+2 ion resulting from the naturally occurring 18 O in the ester function interfering with the M + 2 signal caused by the incorporation of one labelled acetyl-CoA unit. For comparison, we calculated 13 C-incorporation rates of 13 C-glucose-fed wasps also by using the diagnostic ion pair m/z 87/90 [13]. In the samples of the egg-laying experiment, a weak, non-specific signal at m/z 276 was detected in PAME in control samples due to a co-eluting contaminant (7,9-Di-tert-butyl-1-oxaspiro(4,5)deca-6,9-diene-2,8-dione, molecular mass: 276 amu, identification based on mass spectrum and retention time of an authentic reference compound, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…For quantification of FAME in the Nv samples, we integrated the peak areas of the six most abundant FAME (C16 : 0, C16 : 1 Δ9 , C16 : 1 Δ7 , C18 : 0, C18 : 1 Δ9 and C18 : 2 Δ9,12 ) and related them to the peak area of the internal standard C24. Raw data are available from the Dryad Digital Repository: https://doi.org/10.5061/ dryad.d2547d82p [44].…”
Section: (D) Transesterification Of Lipids For Gas Chromatography/ Mass Spectrometry Analysismentioning
confidence: 99%
“…Data accessibility. All relevant data of this paper are available from the Dryad Digital Repository: https://doi.org/10.5061/dryad.d2547d82p [44].…”
mentioning
confidence: 99%